Dihydromyricetin Alleviates Pulmonary Fibrosis by Regulating Abnormal Fibroblasts Through the STAT3/p-STAT3/GLUT1 Signaling Pathway - Li, Zhen; Geng, Jing; Xie, Bingbing; He, Jiarui; Wang, Jing; Peng, Liang; Hu, Yinan; Dai, Huaping; Wang, Chen (Frontiers in Pharmacology, 2022)
Background: Idiopathic pulmonary fibrosis (IPF) is a chronic and progressive disorder with poor prognosis. Dihydromyricetin (DHM), extracted from vine tea and other ampelopsis, even though has been proved to have anti-inflammation and anti-oxidative functions, the effects of DHM on IPF still remains unclear. Methods: The effects of DHM on the differentiation, migration, proliferation and respiratory functions on primary mouse lung fibroblasts (PMLFs) and primary human lung fibroblasts (PHLFs) were detected by western blot, transwell assay, EdU staining and Mito Stress Test. Then the impacts of DHM on bleomycin (BLM)-induced pulmonary fibrosis were evaluated by pathological staining, western blot and co-immunofluorescent staining. The signaling pathway influenced by DHM was also investigated. Results: DHM could regulate the differentiation of fibroblasts to myofibroblasts and suppresses the abnormal migration, proliferation and respiratory functions of myofibroblasts induced by TGF-β1 or myofibroblasts from the IPF patients. It could also alleviate the pulmonary fibrosis induced by BLM. All these functions were achieved by regulating the STAT3/p-STAT3/GLUT1 signaling pathway. Conclusion: DHM could regulate the abnormal functions of myofibroblasts induced by TGF-β1 or that from IPF patients and alleviated pulmonary fibrosis induced by BLM, it might be a candidate medicine for IPF treatment.